2011
DOI: 10.1111/j.1365-3091.2011.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial influence on erosion, grain transport and bedform genesis in sandy substrates under unidirectional flow

Abstract: Interpreting the physical dynamics of ancient environments requires an understanding of how current‐generated sedimentary structures, such as ripples and dunes, are created. Traditional interpretations of these structures are based on experimental flume studies of unconsolidated quartz sand, in which stepwise increases in flow velocity yield a suite of sedimentary structures analogous to those found in the rock record. Yet cyanobacteria, which were excluded from these studies, are pervasive in wet sandy enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…On the other hand, deformed microbial structures are the more outstanding structure to be found in a sedimentary cross-section; in that sense, involuted structures ( Fig. 7c) may indicate that folds and roll-up structures can be later preserved as those mentioned by Hagadorn and McDowell (2012) in ancient environments.…”
Section: Cross-section Sediment Profilesmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, deformed microbial structures are the more outstanding structure to be found in a sedimentary cross-section; in that sense, involuted structures ( Fig. 7c) may indicate that folds and roll-up structures can be later preserved as those mentioned by Hagadorn and McDowell (2012) in ancient environments.…”
Section: Cross-section Sediment Profilesmentioning
confidence: 95%
“…The first ones entangle particles, and most of the motile benthic microorganisms present in the surface are embedded in highly adhesive mucilages, collectively known as EPS (extracellular polymeric substances, Decho, 1990). Consequently, the characteristics of sediments are altered, thus increasing the erosive critical threshold in aquatic environments under unidirectional currents (Hagadorn and McDowell, 2012); tidal currents (Noffke, 2010), and even wave-shear stress (Cuadrado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments and field measurements have demonstrated that bedforms can be inhibited from forming (Hagadorn and McDowell, 2012) and stabilized once formed (Grant et al, 1986) due to biological cohesion from extracellular polymeric substances (EPS) produced by benthic organisms. Recent laboratory experiments using mixed cohesive and non-cohesive sediment, and with added bacterial polymers as a proxy for natural biogenic stabilization, have shown that the dimensions of sedimentary bedforms decrease with increasing bed clay fraction and that the development rate of the bedforms is reduced by both physical and biological cohesion (Baas et al, 2013;Malarkey et al, 2015;Schindler et al, 2015;Parsons et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bioturbation is another subject that calls for coupled physico-chemico-biological studies. Seabed erodibility is largely affected by algae, seagrasses, polychaete worms or cyanobacteria [152,[330][331][332][333]. In addition, there are many examples of coastal ecosystem-based management (see [334]) where interdisciplinarity is requested.…”
Section: A Topic That Moves Forward Through Interdisciplinary Approachesmentioning
confidence: 99%